Effects of live yeast (Saccharomyces cerevisiae Strain 1026) : supplementation on the closure of articular growth plates in quarter horse foals - Perrone, Gustavo Mario (2013)
Fil: Perrone, Gustavo Mario. Universidad de Buenos Aires. Facultad de Ciencias Veterinarias; Argentina